Skewness and Kurtosis Trades - Wolfgang Karl Härdle; Oliver J. Blaskowitz; Peter Schmidt (Humboldt-Universität zu Berlin, Center for Applied Statistics and Economics (CASE), 2004)
In this paper we investigate the profitability of ?skewness trades? and ?kurtosis trades? based on comparisons of implied state price densities versus historical densities. In particular, we examine the ability of SPD comparisons to detect structural breaks in the options market behaviour. While the implied state price density is estimated by means of the Barle and Cakici Implied Binomial Tree algorithm using a cross section of DAX option prices, the historical density is inferred by a combination of a non?parametric estimation from a historical time series of the DAX index and a forward Monte Carlo simulation.
Keywords: 330